Exploring the Dual Impact of AI on Employment and Wages in Chinese Manufacturing - Wang, Jing (SEISENSE Journal of Management, 2024)
Purpose- This study investigates AI's impact on employment and wage dynamics within the manufacturing sector.Design/Methodology- Utilizing data from 3,522 manufacturing firms between 2007 and 2021, we analyze the effects of AI adoption on labor markets. Findings- AI adoption correlates with reduced employment numbers yet enhances wage rates, with some employees seeing wage increases as high as 83.86%. Heterogeneity analysis reveals variability in these impacts, dependent on contextual factors. The deployment of artificial intelligence in manufacturing sectors leads to an upgraded wage structure, emphasizing the importance of advancing individual professional skills to capitalize on these wage improvements. Additionally, compared to larger firms in the eastern region, small and medium-sized enterprises in the central and western regions stand to gain more substantially from the integration of artificial intelligence technology.Practical Implications- Policymakers need targeted interventions to address job losses while leveraging wage growth benefits, emphasizing reskilling and inclusive AI integration strategies. The study provides empirical evidence on AI's dual effect on employment and wages, offering nuanced insights into sector-specific AI consequences.